Invisible transitions: Transitions to school following different paths. Issue 3 (September 2021) - Dockett, Sue; Perry, Bob
Most children starting primary school in Australia do so after attending early childhood education and participating in a transition to school programme. While this has become the expected pathway, it is not the one followed by all children and their families. In this article, we describe visible transitions as those that are known, understood and planned – that is, they follow the expected path. In contrast, invisible transitions occur when children and families arrive unexpectedly at school. Drawing on two studies involving 30 schools in two different states of Australia, we report the scope and nature of invisible transitions and the challenges and opportunities arising from invisible transitions in these schools. Each of the schools reported instances of invisible transitions. Some, but not all, schools promoted strategies involving school staff, other families and children to support those arriving unexpectedly. While invisible transition was identified as a challenge, the opportunities for reflecting on existing transition approaches and building inclusive strategies were also noted.